Anfänge bei Hegel - Schmied-Kowarzik, Wolfdietrich (Kassel University Press, 2008)
This anthology assembles several contributions held at the symposium "Beginnings at Hegel" on occasion of the 70th birthday of Helmut Schneider on 2 July 2008 at the University of Kassel. Several further articles round off the volume to a comprehensive study book on Hegel.